Meanings About Educational Counselling: A Case Study - Carrasco-Aguilar, Claudia; Elgueta, Daniela; Olivares, Belén; Baltar, María Julia; Alfaro, Nancy; Figueroa, Marlen (Revista de Psicología, 2019)
Since the enacting of the Preferential School Subsidy Law, several educational technical support agencies (ETSA; acronym in Spanish) began to offer consultancy as private organizations to requesting educational institutions committed with policies of educational standardization and accountability. National and international literature remark that effective consultancy focusses on participation and collaboration, emphasizing a pertinent consultancy as key on school improvement. The present study used a qualitative approach, analyzing the axis of meanings of a consultancy team within an ETSA, working with two municipal schools differing in the level of school performance. A content analysis was used on interviews showing two categories. These show the presence of tension regarding the role of consultants about participation and directivity; as well as the relevance of context on the meanings about the consultant. Results are discussed around the axis of meaning in tension, the negotiation, the values of the consul-tancy and the macrosocial, institutional and school context.